Photocatalytically Active Titania Produced by MOCVD Plasma Process - Moser, Eva Maria; Chappuis, Sidney; Olleros, Javier (International Conference on Plasma Surface Engineering, 2013)
The deposition of photocatalytically active titania layers at ambient temperature was developed using the plasma enhanced metal organic chemical vapour deposition (PE-MOCVD) method at low and atmospheric pressure. An increase of the photo-activity in the near ultraviolet (UV) and blue light irradiation was achieved by doping the titania layers using the elements nitrogen and/or carbon. Investigation of the chemical and structural features of the titania layers was carried out by x-ray photoelectron spectroscopy, atomic force microscopy, and Raman. The optical energy bandgap and photocatalytic activity at 365/428 nm for various titania layers were analyzed using ellipsometry and the methylene blue dye bleaching according to ISO 10678:2010, respectively. The reduction of the aqueous methylene blue solution was similar for the two categories of titania layers. However, the photo-induced properties such as the mineralization of stearic acid for investigating anti-fingerprint effects evidenced a weaker interaction between the mostly hydrophobic PE-MOCVD titania surfaces than for the hydrophilic and rougher PVD produced titania layers when irradiated under UV light. The observed differences were related to the chemical and structural features since the hydrophobic PE-MOCVD produced titania layers were amorphous and nitrogen and carbon incorporation into TiO2 led to an enhanced photocatalytic ability by a factor of two regarding the dye tests, whereas the energy bandgap remained at about 3.2 eV. Substitutional and interstitial doping of nitrogen and/or carbon was evidenced by XPS. An additional benefit regarding the adhesion and abrasion resistance was observed for the tailored doping of titania layers.